Dissemination of Employment Law to the Community of Carenang Village as a Sister Village for the East Serang Industrial Zone - Agus, Dede (Probono and Community Service Journal, 2024)
The phrase where there is society there is law (ubi societas ibi ius) and "Indonesia is a state of law", means that the consequences of all society's activities must be based on law, including industrial relations activities. Industrial relations, such as: pre-employment, during employment and post employment, are regulated by labor law. Residents of Carenang Village are in contact with industrial relations activities due to their proximity to the East Serang industrial zone. Therefore, it has become a target village in labor law socialization activities, as well as being a location for KKM Group 61 service at Sultan Ageng Tirtayasa University.